2017
DOI: 10.1007/s11010-016-2919-3
|View full text |Cite
|
Sign up to set email alerts
|

Physiology of the Vc-NhaP paralogous group of cation–proton antiporters in Vibrio cholerae

Abstract: The genome of Vibrio cholerae encodes three cation-proton antiporters of NhaP-type, Vc-NhaP1, 2, and 3. To examine physiological roles of Vc-NhaP antiporters, triple ΔnhaP1ΔnhaP2ΔnhaP3 and single ΔnhaP3 deletion mutants of V. cholerae were constructed and characterized. Vc-NhaP3 was, for the first time, cloned and biochemically characterized. Activity measurements on the inside-out membrane vesicle experimental model defined Vc-NhaP3 as a potassium-specific cation-proton antiporter. While elimination of functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…Mammalian NHE has high homology with the bacterial NhaP family, while it has low homology with the bacterial NhaA family, a member of the bacterial Na + /H + antiporter family ( Waditee et al, 2001 ; Resch et al, 2011 ; Padan and Landau, 2016 ). In addition, the NhaP antiporter family has been shown to have a large hydrophilic domain at its carboxy-terminal side like NHE ( Waditee et al, 2001 ; Mourin et al, 2017 ).…”
Section: Diversity Of Na + /H + mentioning
confidence: 99%
“…Mammalian NHE has high homology with the bacterial NhaP family, while it has low homology with the bacterial NhaA family, a member of the bacterial Na + /H + antiporter family ( Waditee et al, 2001 ; Resch et al, 2011 ; Padan and Landau, 2016 ). In addition, the NhaP antiporter family has been shown to have a large hydrophilic domain at its carboxy-terminal side like NHE ( Waditee et al, 2001 ; Mourin et al, 2017 ).…”
Section: Diversity Of Na + /H + mentioning
confidence: 99%
“…The NQR is a membrane-bound flavo-iron sulfur protein complex composed of six subunits (9). The enzyme is of central importance for V. cholerae, since the electrochemical Na ϩ gradient generated by the NQR drives many other cellular processes, such as flagellar rotation, exchange of cations, and expulsion of antibiotics (10)(11)(12).…”
mentioning
confidence: 99%
“…In particular, V. cholerae encodes three NhaP type antiporters, encoded by paralogous structural genes Vc-nhaP1 , 2 , and 3 , mediating the exchange of K + and Na + for protons [3,4]. We found that all three Vc-NhaP-type antiporters exchange K + for H + in vivo and operate in concert to maintain the viability of V. cholerae cells in acidic, especially K + -rich environments [5]. Vc-NhaP2 seems to be a major component of this trio [5].…”
Section: Introductionmentioning
confidence: 99%
“…We found that all three Vc-NhaP-type antiporters exchange K + for H + in vivo and operate in concert to maintain the viability of V. cholerae cells in acidic, especially K + -rich environments [5]. Vc-NhaP2 seems to be a major component of this trio [5]. At the physiological level, the importance of the entire NhaP group for survival of V. cholerae at low pHs indicated its possible role at the critical step of the natural infectious process, when ingested V. cholerae passes the gastric acid barrier.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation